Kebebasan Morfologis dalam Budaya Konsumen Human Enhancement Technology: Studi Kasus Budaya Konsumen Obat Non-Terapeutik pada Pemuda - Abdussalam, Sony Matin (UI Scholars Hub, 2017)
Nowadays, technological innovations and sciences have reached the stage of modification and improvement of the capacity of the human body. This technology varies from prosthetic devices, implants, plastic surgery, drugs, genetic engineering, nanotechnology, and others. Several previous studies have shown that the advancement of this technological intervention has created a consumer culture of human enhancement products and services, for instance, non-therapeutic drugs. However, previous discussions about human enhancement products and services failed to provide further explanation on morphological freedom from the perspective of consumer culture. Morphological freedom is an individual right to modify or otherwise, refuse to modify one’s physical form that manifested in the use of human enhancement technology (HET). Provided the circumstances, this study aimed to discuss morphological freedom in the consumption of non-therapeutic drugs from one perspective of consumer culture framework, which is ‘imagination, joy, and satisfaction from consumption’. This study which used case study method on 9 people ranging from 16 to 30 years of age has generated three arguments. First, morphological freedom emerges after a condition called morphological consciousness. Second, in the context of Indonesian consumer society, morphological freedom is justified by individual religious norms and values. Third, morphological freedom produces a consumer culture of non-therapeutic drugs that manifested in a form of lifestyle.